Susceptibility Of Different Silkworm Breeds To Nuclear Polyhedrosis And Bacterial Flacherie Under Natural Conditions (Applied Biological Research, 2016)
Silkworm, Bombyx mori (L.), is susceptible to several diseases and no  breed so far is reported to be immune. In the present investigations, 41  silkworm breeds of varied geographical origin were evaluated for their susceptibility to Bombyx mori nuclear polyhedrosis (BmNPV) and  bacterial flacherie under natural conditions. Significant difference was  observed in larval and pupal mortality due to both nuclear polyhedrosis  and bacterial flacherie. The highest larval mortality (9.29%) was  observed in ‘M57’ due to nuclear polyhedrosis and least (0.77%) in  ‘NB4D2’ and ‘SI(P)’. The larval mortality due to flacherie ranged from  0.67 to 7.22%. A significant variation was observed in pupation rate and  highest pupation was noticed in ‘Jam10’ (95.31), followed by ‘S1M’ (95.27), ‘BL1’(95.10), ‘CP1A’(94.66), ‘Pure81’, (94.56), ‘CPIB’ (94.33),  ‘S1P’(94.21), ‘Chinese Farmer’ (94.19), ‘Chakwi’ (94.09) and ‘Chinese  D4’(94.03) which were statistically at par with one onother.
Keywords: Breeding; Bombyx mori nuclear polyhedrosis; flacherie; silkworm; susceptibility